Analysis of Engineered Tobacco Mosaic Virus and Potato Virus X Nanoparticles as Carriers for Biocatalysts - Schuphan, Juliane; Commandeur, Ulrich (Frontiers in Plant Science, 2021)
Plant virus nanoparticles are promising candidates for the development of novel materials, including nanocomposites and scaffolds/carriers for functional molecules such as enzymes. Their advantages for enzyme immobilization include a modular organization, a robust and programmable structure, and simple, cost-effective production. However, the activity of many enzymes relies on post-translational modification and most plant viruses replicate in the cytoplasm, so functional enzymes cannot be displayed on the virus surface by direct coat protein fusions. We recently developed an alternative display system to present the Trichoderma reesei endoglucanase Cel12A on potato virus X (PVX) using SpyTag/SpyCatcher (ST/SC) technology, which allows the carrier and enzyme to be produced separately before isopeptide conjugation. Although kinetic analysis clearly indicated efficient biocatalyst activity, the PVX carrier interfered with substrate binding. To overcome this, we tested the suitability of tobacco mosaic virus (TMV), which can also accommodate a larger number of ST peptides. We produced TMV particles displaying ST as a new platform for the immobilization of enzymes such as Cel12A, and compared its performance to the established PVX-ST platform in terms of catalytic efficiency. Although more enzyme molecules were immobilized on the TMV-ST particles, we found that the rigid scaffold and helical spacing significantly affected enzyme activity.